Soft Skills and Learning Facilities on Job Readiness Mediated by Learning Motivation of Vocational High School - Kamal, Annisa Septiani; Syahrul, Syahrul; Arfandi, Anas (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Dompu Regency vocational high school graduates are expected to be job-ready, yet many struggle to fulfill industry standards. Technical capabilities are generally stressed, but student drive, learning infrastructure, and soft skills are significant but understudied aspects affecting professional preparation. This study examines how Dompu Regency vocational high school students' learning motivation mediates the effect of soft skills and learning facilities on work preparedness. The study was quantitative and ex post facto. The sample included 211 grade XI students selected by cluster selection and proportional random sampling to represent regency schools. Structured equation modeling using partial least squares was used to examine data. The results show that soft skills have a significant effect on work readiness (β = 0.395; p = 0.000) and learning motivation (β = 0.621; p = 0.000). Learning facilities also significantly influence work readiness (β = 0.139; p = 0.006) and learning motivation (β = 0.216; p = 0.000). Furthermore, learning motivation significantly influences work readiness (β = 0.413; p = 0.000) and serves as a vital mediator for both soft skills and learning facilities. These findings underscore that work readiness is not merely a product of external resources but is heavily driven by the student's internal motivation developed during the learning process. The "mediation mechanism" of motivation is empirically supported in this vocational education study. It gives Dompu Regency schools and policymakers a framework to emphasize physical infrastructure, soft skill integration, and psychological motivational tactics to boost graduate employability.